2002
DOI: 10.3989/scimar.2002.66s255
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, abundance and biological features of anglerfish (<i>Lophius piscatoirus</i> and <i>Lophhius budegassa</i>) (Osteichthyes: Lphiiformes) in the Mediterranean Sea

Abstract: SUMMARY:The distribution and biological features of anglerfish (Lophius piscatorius and L. budegassa) in the Mediterranean Sea were analysed from trawl surveys data (MEDITS project, years 1994(MEDITS project, years -1999. The above-mentioned species were widely distributed in the Mediterranean, but differences in abundance were found according to geographic sectors and depths. Most of the collected specimens belonged to the first length cohorts and length distributions also differed at macroarea levels. Mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 8 publications
6
27
3
Order By: Relevance
“…These results agree with those obtained in studies that were focused on the northeastern Atlantic Ocean, where this species spawns from November through June (Fulton, 1898; Afonso-Dias and Hislop, 1996;Hislop et al, 2001). However, a previous study in the northwestern Mediterranean Sea identified a spawning season during spring-summer (Ungaro et al, 2002). Discrepancies between the latter study and our work may be explained by the differences in sampling periods.…”
Section: Relevance Of Reproductive Traits For Sustainable Managementcontrasting
confidence: 56%
See 1 more Smart Citation
“…These results agree with those obtained in studies that were focused on the northeastern Atlantic Ocean, where this species spawns from November through June (Fulton, 1898; Afonso-Dias and Hislop, 1996;Hislop et al, 2001). However, a previous study in the northwestern Mediterranean Sea identified a spawning season during spring-summer (Ungaro et al, 2002). Discrepancies between the latter study and our work may be explained by the differences in sampling periods.…”
Section: Relevance Of Reproductive Traits For Sustainable Managementcontrasting
confidence: 56%
“…Studies conducted in the Mediterranean Sea have been scarce, and they have been focused on temporal and spatial distribution of this species (Ungaro et al, 2002;Colmenero et al, 2010), age and growth (Tsimenidis and Ondrias, 1980;Tsimenidis, 1984), feeding ecology (López et al, 2016), morphometrics (Negzaoui-Garali and Ben Salem, 2008), parasites (Colmenero et al, 2015a), and ova characteristics (Colmenero et al, 2015b). Among these studies, only Ungaro et al (2002) analyzed some of the biological features of this species by using data available from trawl surveys, including data on distribution, abun- dance, stock demography, and size at maturity. The latter work is valuable but is limited because sampling occurred only in the spring and summer; a whole year of sampling is recommended to obtain more accurate biological information.…”
mentioning
confidence: 99%
“…This angler is a cold-water species, whose presence in the deeper waters of the northern parts of the Mediterranean and Black Seas may be an iceage relict, as indicated for other boreal coldwater fishes with isolated populations in the Mediterranean (Briggs, 1974, p. 206). In fact there are two species of Lophius in the Mediterranean region, and the second species, L. budegassa, is more prevalent (Ungaro et al, 2002); a situation reversed in the North-East Atlantic. It may be that P. gracilescens (s.…”
Section: Discussionmentioning
confidence: 97%
“…In European Atlantic waters, studies include those of growth (Dupouy et al, 1986;Peronnet et al, 1992;Duarte et al, 1997;Landa et al, 1998Landa et al, , 2001aLanda et al, , 2001bQuincoces et al, 1998), reproduction (Azevedo, 1996a;Duarte et al, 1998;Quincoces et al, 1998), feeding and trophic chains (Olaso et al, 1982;Crozier, 1985;Pereda and Olaso, 1990;Azevedo, 1996b), as well as the geographic and bathymetric distribution (Caruso, 1985;Vasconcelos et al, 1986;Azevedo and Pereda, 1994;Azevedo, 1995). In the Mediterranean, the understanding of the biology of the species is even more limited since there are only a few existing studies (Tsimenidis and Ondrias, 1980;Campillo et al, 1989and Bertrand, 1991, summarized in Quesada, 1991García-Rodríguez and Esteban, 1998;Ungaro et al, 2002) that refer to some aspects of their biology and fishing.…”
Section: Introductionmentioning
confidence: 95%